Assessment of genetic variability and heritability of vegetative, floral and fruit traits in tomato (Solanum lycopersicum L.) (Zoo Botanica, 2025)
Genetic diversity is crucial for tomato (Solanum lycopersicum L.) improvement. To assess this variability, a field experiment was conducted using eleven tomato varieties arranged in randomized complete block design with five replications. This study was designed to estimate genetic parameters for 19 vegetative and reproductive traits. Statistical analysis revealed significant differences among the genotypes for the majority of the traits, confirming the presence of substantial genetic diversity. The estimates of genotypic and phenotypic coefficients of variation (GCV and PCV) were highest for pulp weight and leaf rachis length, indicating a strong inherent genetic potential for selection. Fruit length recorded the highest genotypic (85.88) and phenotypic (104.44) variances. Heritability estimates were high for most traits crucial for yield, with the maximum value observed for fruit length (0.82). The combination of a pronounced level of heritability and substantial expected genetic advance for these traits appears to suggest that their expression is primarily controlled by gene action. Therefore, future breeding programs should prioritize direct selection for characters such as fruit length, pulp weight, and leaf architecture to achieve rapid genetic gain and enhance tomato yield productivity.
Keywords: Tomato; genetic variability; heritability; morphological characterization; coefficient of variation